2019
DOI: 10.1029/2018ea000529
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Fertilization Confounds Tree‐Ring Records of Regional Hydroclimate at Northeastern Qinghai‐Tibetan Plateau

Abstract: Understanding historical hydroclimate change during the last millennium is of fundamental importance for forecasting and evaluating the regional hydrologic cycle and water security under global warming. Here we compared observations of tree‐ring stable isotope ratios (δ13C and δ18O), tree‐ring widths, lake sediments estimates of regional hydroclimate, and glacier advance and retreat for northeastern Qinghai‐Tibetan Plateau, China. The hydroclimate dynamics in our composite isotope record is similar to that der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The reactions generating the lowest δ 13 C values occur if the c i level increases proportionally with pCO 2 (c at -c i constant; passive response), and the lowest effects on the tree-ring δ 13 C values occur if c i /c at stays constant (active response; Saurer et al, 2004). The phenomenon is especially marked after 1955 -above 330 ppm of CO 2 -when the pressure rise is acute (e.g., Waterhouse et al, 2004). But cases of no isotopic responses to rising pCO 2 exist as well (δ 13 C constant; Silva and Horwath, 2013;Belmecheri et al, 2014;Wieser et al, 2016;Savard et al, 2020).…”
Section: Physiological Effects Of Rising Pcomentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions generating the lowest δ 13 C values occur if the c i level increases proportionally with pCO 2 (c at -c i constant; passive response), and the lowest effects on the tree-ring δ 13 C values occur if c i /c at stays constant (active response; Saurer et al, 2004). The phenomenon is especially marked after 1955 -above 330 ppm of CO 2 -when the pressure rise is acute (e.g., Waterhouse et al, 2004). But cases of no isotopic responses to rising pCO 2 exist as well (δ 13 C constant; Silva and Horwath, 2013;Belmecheri et al, 2014;Wieser et al, 2016;Savard et al, 2020).…”
Section: Physiological Effects Of Rising Pcomentioning
confidence: 99%
“…This six-step non-linear detrending of the low-frequency changes (McCarroll et al, 2009) works better when the measured δ 13 C series starts before or at the beginning of the industrial period (1850); otherwise the method might undercorrect the δ 13 C values (Schubert and Jahren, 2012). As in the proportional correction, the pin model assumes that the tree responses to rising pCO 2 are linear and uniform even if sometimes the responses are non-linear for a given tree and heterogeneous amongst trees (Waterhouse et al, 2004;Mc-Carroll et al, 2009). The approach pointedly applies a nonlinear regression to trees, a step that considers the pCO 2induced response specific to each tree.…”
Section: Physiological Effects Of Rising Pcomentioning
confidence: 99%
“…The multi-proxy approach combines two or more records of different tree-ring variables (ring width, wood density, cellulose  13 C,  18 O (or  2 H) values, cell wall thickness, tracheid-lumen diameter, or other wood anatomical traits) measured at the same site. Indeed, combining proxies with the same dominant control, but different secondary controls, tends to accentuate the common climate signal (McCarroll et al, 2011;Gennaretti et al, 2017;Wang et al, 2019). If a process generating divergence does not affect the tree-ring proxies in the same way, combining several different proxy records can help reduce the amplitude of divergence between the climate signal and its reconstruction.…”
Section: Approaches To Avoid Isotopic Divergences Due To Change In CLmentioning
confidence: 99%
“…However, there are still confusing problems in tree‐ring data, mainly including tree‐ring width and iWUE derived from tree‐ring δ 13 C ratio. For examples, in some studies, iWUE can lead to enhanced tree growth (Huang et al ., 2007; 2017; Liu et al ., 2014; Lu et al ., 2018; Wang et al ., 2018; 2019; Wu et al ., 2018; 2020). Nevertheless, other studies have found that higher value of iWUE were significantly related to forest mortality (Linares and Camarero, 2012; Silva and Anand, 2013; Wu et al ., 2015; Sun et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The ecological environment is relatively fragile, and tree growing here is more sensitive to climate change. Some studies in this region have explored the linkages between tree‐ring δ 13 C ratio and climatic factors (Liu et al ., 2007a; 2007b; 2008; 2014; Wang et al ., 2019; 2021). And the main tree species in the Qilian Mountains, such as Qinghai Spruce ( Picea crassifolia Kom.)…”
Section: Introductionmentioning
confidence: 99%